The problem of traditions in the works of sergey esenin - Kurbanova Mukaddas Omonovna; Ibragimova Zumrad Tolipovna (Research Parks Publishers, 2021)
The article presents a model of perception of the artistic tradition of Pushkin in the works of the national poet Sergei Yesenin. The features of the Russian approach to the selection of cultural values that formed the basis of the artistic tradition are considered. On the example of Yesenin’s poetry, a timely interpretation of the works of traditional national literature, the originality of the approach to the Russian artistic tradition is shown.